Pengaruh Self-Efficacy terhadap Work Readiness Mahasiswa Gen Z dengan Career Planning sebagai Mediasi - Febrianti, Bella Ayu; Ingsih, Kusni; Farida, Ida; Sartika, Mila (Jurnal EMT KITA, 2026)
This study uses career planning to evaluate how self-efficacy affects Gen Z students' work preparation. The study included Central Java public and private university students. A proportionate random sample of 110 respondents was chosen. Quantitative analysis used SEM-PLS version 3. The results show that self-efficacy improves career planning and employment preparation. Direct and indirect effects show the importance of self-confidence in career planning and work readiness. Career planning somewhat mediates self-efficacy-work readiness. These findings suggest that Gen Z students' work preparation is best improved by boosting self-efficacy and career planning.